Fabrication and Time Degradation Study of Mercuric Iodide (Red) Single Crystal X-Ray Detector - Kulvinder Singh; Manoj Saxena (Журнал нано- та електронної фізики)
Mercuric iodide is well known semiconductor solid state X-ray detector. Stability of Mercuric Iodide detector is one of the major problems to its practical applications. In the present work, single crystal of mercuric iodide was grown from a well purified material and detector is fabricated on a fused quartz base with platinum electrodes. Degradation of detector is studied and analyzed.